2006
DOI: 10.1179/174328106x113959
|View full text |Cite
|
Sign up to set email alerts
|

Use of waste plastics in cokemaking at Tata Steel

Abstract: Disposal of waste plastics is a serious global issue, and hence it is imperative to explore methods to recycle them for efficient utilisation. The coke making process is considered to be a promising area to which the thermal decomposition of waste plastics is applicable, because the process involves coal carbonisation at a high temperature under a reducing atmosphere. As an outcome of the research work carried out on a laboratory scale followed by plant trials at Tata Steel, it was found that waste plastics re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The carbonization of coal to produce metallurgical coke is considered as one possible route for recycling plastic wastes of different structure and origin. Recently, integrated steel plants made a further contribution to plastics recycling by applying it to the blast furnace [1][2][3][4][5][6] and the carbonization processes [7][8][9][10][11][12][13][14][15][16]. In 2000, the Nippon Steel Corporation (NSC) began the industrial application of plastic wastes as minor components of coal blends for blast-furnace coke production at the Nagoya and Kimitsu works with a recycling capacity of 80,000 t/year [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The carbonization of coal to produce metallurgical coke is considered as one possible route for recycling plastic wastes of different structure and origin. Recently, integrated steel plants made a further contribution to plastics recycling by applying it to the blast furnace [1][2][3][4][5][6] and the carbonization processes [7][8][9][10][11][12][13][14][15][16]. In 2000, the Nippon Steel Corporation (NSC) began the industrial application of plastic wastes as minor components of coal blends for blast-furnace coke production at the Nagoya and Kimitsu works with a recycling capacity of 80,000 t/year [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As for the effect of plastic type, there have been many studies on the influence of plastic addition on coal-caking property and coke quality [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. It was revealed that thermal decomposition products of plastics interacted with bituminous coal during carbonization in a coke oven.…”
Section: Influence Of Plastic Addition On Coke Qualitymentioning
confidence: 99%
“…During non-blast furnace ironmaking, the gas-based reduction process is implemented using pressure. Many experts' studies on the mechanism of inhibiting sticking loss are mostly based on atmospheric pressure and differ from the production practice.In order to improve environmental protection and production efficiency, the current study added energetic waste plastics into the iron ore powder [16] according to a certain size and ratio, resulting in the changing direction of the optimal operating parameters in a self-designed, hot visual, pressurized, fluidized bed experimental device. On this basis, economic, convenient, and effective operating parameters were determined.…”
mentioning
confidence: 99%
“…In order to improve environmental protection and production efficiency, the current study added energetic waste plastics into the iron ore powder [16] according to a certain size and ratio, resulting in the changing direction of the optimal operating parameters in a self-designed, hot visual, pressurized, fluidized bed experimental device. On this basis, economic, convenient, and effective operating parameters were determined.…”
mentioning
confidence: 99%